Process Parameter Optimization for Friction Stir Welding of AA6061 and AA7075 - L. H., Shah; N. F., Zainal Ariffin (2014)
In this study, the Taguchi method was utilized to determine the optimum process parameters for friction stir welding between AA6061 and AA7075 aluminium alloys. The Taguchi L9 orthogonal array and optimization approach was applied on three levels of three critical factors, namely rotational speed, transverse speed and tool tilt angle. The optimum levels of process parameters were determined through the Taguchi parametric design approach. Through the analysis, the predicted value of the dissimilar joint's tensile strength was calculated to be 210 MPa, which is in close proximity to the experimental data.